1991
DOI: 10.1007/bf00200543
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and accumulation of ribosomes in individual cells of the female gametophyte of maize during its development

Abstract: Summary. The pattern of synthesis of ribosomes during three stages of development of the female gametophyte of maize has been studied by in situ hybridization using a ribosomal RNA probe. Changes in volume of individual cells of the embryo sac during its maturation have been determined by confocal microscopy. These data have permitted us to calculate the relative numbers of ribosomes in the cells of the embryo sac at different stages of their maturation. The egg apparatus and the central cell at all stages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…A high level of ribosomes in the cells of the embryo sac, including the egg cell, was observed earlier in Zea (Dow and Mascarenhas 1991a , b ). Investigations using the in situ hybridization method with a probe for 25S rRNA indicated that the number of ribosomes increases during the development of the embryo sac, reaching the highest level during its maturity.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…A high level of ribosomes in the cells of the embryo sac, including the egg cell, was observed earlier in Zea (Dow and Mascarenhas 1991a , b ). Investigations using the in situ hybridization method with a probe for 25S rRNA indicated that the number of ribosomes increases during the development of the embryo sac, reaching the highest level during its maturity.…”
Section: Discussionsupporting
confidence: 61%
“…During this period, intensive transport of newly formed ribosomal subunits to the cytoplasm also occurs, which is indicated by a high rRNA signal at the boundary between the nucleus and the cytoplasm. The process of ribosome accumulation in the cytoplasm of the maturing central cell was previously observed in Zea (Dow and Mascarenhas 1991a , b ). Our investigations indicate that, in H. orientalis , ribosome maturation also takes place during the progamic phase.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Such in situ hybridization analyses have enabled us to determine the relative numbers of ribosomes in the cells of the mature female gametophyte and also in immature stages of embryo sac development (Dow and Mascarenhas 1991).…”
Section: Discussionmentioning
confidence: 99%
“…During female gametogenesis, the haploid functional megaspore undergoes continuous cell growth and three cycles of consecutive nuclear division without cytokinesis, giving rise to a giant eight-nucleate, coenocytic cell: the embryo sac. The size of the embryo sac increases about 6-fold without cytokinesis until it reaches its maximum during gametogenesis in maize (Zea mays; Dow and Mascarenhas, 1991). The two polar nuclei migrate toward the micropylar half of the embryo sac and eventually fuse to give rise to a diploid nucleus of the central cell.…”
mentioning
confidence: 99%